Separating Energetic Internal Gravity Waves and Small‐Scale Frontal Dynamics. Issue 6 (15th March 2022) - Torres, Hector S.; Klein, Patrice; D'Asaro, Eric; Wang, Jinbo; Thompson, Andrew F.; Siegelman, Lia; Menemenlis, Dimitris; Rodriguez, Ernesto; Wineteer, Alexander; Perkovic‐Martin, Dragana
Abstract: Oceanic fronts with lateral scales less than 20 km are now known to be one of the major contributors to vertical heat fluxes in the global ocean, which highlights their potential impact on Earth's climate. However, frontal dynamics with time scales less than 1 day, whose contribution to vertical heat fluxes is thought to be significant, are obscured by energetic internal gravity waves (IGWs). In this study, we address this critical issue by separating IGWs and frontal dynamics using an approach based on their respective vertical scales of variability. Results using a numerical model with a horizontal grid spacing of 500 m confirm that it is possible to recover frontal dynamics at short time scales as well as associated intense vertical velocities and vertical heat fluxes. This opens up new possibilities for a more accurate estimation of the vertical exchanges of any tracers between the surface and the ocean interior. Plain Language Summary: Two classes of motions involving large vertical velocities are present in the upper ocean: Those associated with small‐scale fronts (<20 km, also called submesoscale or SBM fronts) and those associated with internal gravity waves (IGWs). SBM fronts are known to explain most of the vertical transport of heat, nutrients, and major gases. IGWs do not transport tracers. Rather, small‐scale IGWs are thought to lead to irreversible mixing through breaking. One issue that arises when analyzing in‐situ observations and numerical simulations is how to discriminate between SBMs and IGWs when both classes of motions are energetic, such as in the California Current System. In this study, we show that SBM fronts and IGWs exhibit different vertical scales, which can be exploited to separate the two classes of motions. Our results confirm that filtering the contribution of large vertical scales to 3‐dimensional velocity fields leads to an almost complete recovery of SBM frontal dynamics at short time scales. The significance of this separation is illustrated by the impact of short‐time‐scale, frontal‐induced vertical velocity on vertical heat fluxes. Key Points: Vertical transport due to convergence at surface fronts is obscured by internal gravity waves in a model of the California Current Contamination by low‐mode internal waves can be reduced by filtering large vertical scales A simple filtering algorithm can effectively remove internal waves with little impact on frontal dynamics in the model